Mixed matrix membrane as well as preparation method and application thereof
By using the covalent organic skeleton and inlaid polyetheride resin using ionic liquid modified in the gas separation membrane, the existing membrane permeability and selectivity are difficult to take into account. Excellent thermal stability and long -term stability.
Patent Information
- Application Number
- CN202411149099.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-08-21
AI Technical Summary
The permeability and selectivity of existing gas separation membranes cannot be taken into account at the same time, making it difficult to efficiently separate carbon dioxide and methane.
The covalent organic skeleton containing ionic liquid modifiers and the mixed matrix membrane of polyetheric amide resin can be used to improve the solubility of the pore diameter of the membrane and carbon dioxide through the modification process, thereby improving the separation performance.
Achieve high permeability and excellent selectivity, suitable for the separation of gas of carbon dioxide and methane, and maintain good performance under different temperature and pressure, with excellent thermal stability and long -term operation stability.
Smart Images

Figure CN119345930A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas membrane separation, and in particular to a mixed matrix membrane and a preparation method and application thereof. Background Art
[0002] With the rapid development of economic globalization and world industrialization, fossil fuels are widely used in life and industry. A large amount of carbon dioxide gas produced by the combustion of fossil fuels is discharged into the air, causing serious greenhouse effects and other environmental problems. The efficient and reasonable development and application of renewable energy is an effective way to solve the current environmental and energy problems. According to the resolution of the United Nations, the use of renewable energy should account for 77% of the world's energy use by 2050. Biogas, also known as biogas, is a low-carbon, environmentally friendly, clean and renewable natural gas. However, untreated biogas contains a large amount of carbon dioxide, which will not only seriously reduce the combustion calorific value of biogas but also corrode the transportation pipeline and cause economic losses. Therefore, the carbon dioxide in biogas must be separated.
[0003] At present, the commonly used methods for separating carbon dioxide are: adsorption, physical or chemical absorption, cryogenic distillation, hydration and membrane separation. Among them, membrane separation has been widely used in commercial applications due to its advantages of low cost, high efficiency and low environmental pollution. According to the different membrane materials, common gas separation membranes are mainly divided into three types: inorganic membranes, organic polymer membranes and mixed matrix membranes. Generally, the preparation process of inorganic membranes is complicated and costly. Although polymer membranes have excellent mechanical properties and the membrane preparation process is simple and controllable, their separation performance is limited by the trade-off effect and cannot improve permeability and selectivity at the same time. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem that the permeability and selectivity of gas separation membranes in the prior art cannot be taken into account at the same time, and to provide a mixed matrix membrane and its preparation method and application. The mixed matrix membrane has high permeability and excellent selectivity, and is particularly suitable for gas separation of carbon dioxide and methane; and under different temperatures and pressures, it can still maintain good overall performance. Under long-term operation, the separation performance of the mixed matrix membrane does not decay, and it has excellent thermal stability and good long-term operation stability.
[0005] In order to achieve the above object, the present invention provides a mixed matrix membrane on one hand, wherein the mixed matrix membrane contains a covalent organic framework modified by an ionic liquid and a block polyetheramide resin.
[0006] Preferably, the content of the ionic liquid-modified covalent organic framework is 0.1-20 parts by weight, preferably 1-5 parts by weight, relative to 100 parts by weight of the block polyetheramide resin.
[0007] Preferably, the ionic liquid-modified covalent organic framework is a Dha Tab-COF framework modified by ionic liquid.
[0008] Preferably, during the modification process, the mass ratio of the Dha Tab-COF framework to the ionic liquid is 1:(4-10), preferably 1:(5-7).
[0009] Preferably, the ionic liquid is at least one of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and 1,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide.
[0010] Preferably, the mixed matrix membrane has a thickness of 1.3-2.2 microns.
[0011] A second aspect of the present invention provides a method for preparing the mixed matrix membrane as described above, the method comprising the following steps:
[0012] (1) modifying the covalent organic framework with an ionic liquid to obtain an ionic liquid-modified covalent organic framework;
[0013] (2) The ionic liquid-modified covalent organic framework is mixed with a block polyether amide resin solution, and the obtained mixture is coated on a porous base membrane, and then allowed to stand and dried.
[0014] Preferably, in step (1), the process of modifying the covalent organic framework with an ionic liquid comprises the following steps:
[0015] S1: vacuum treating the covalent organic framework;
[0016] S2: mixing the ionic liquid with the organic solvent, and mixing the obtained mixed liquid with the vacuum-treated covalent organic framework;
[0017] S3: The mixture obtained after the treatment in step S2 is centrifuged, and then the separated solid is washed and dried.
[0018] Preferably, the mass ratio of the covalent organic framework to the ionic liquid is 1:(4-10), preferably 1:(5-7).
[0019] Preferably, the covalent organic framework is a Dha Tab-COF framework.
[0020] Preferably, the ionic liquid is at least one of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and 1,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide.
[0021] Preferably, in step (2), the mass ratio of the ionic liquid-modified covalent organic framework to the block polyetheramide resin is (0.1-20):100, preferably (1-5):100.
[0022] Preferably, the concentration of the block polyetheramide resin solution is 2-10 wt %, more preferably 4-6 wt %.
[0023] Preferably, in step (2), the porous base membrane is a polyvinylidene fluoride membrane supported by a polyester non-woven fabric.
[0024] The third aspect of the present invention also provides the use of the mixed matrix membrane described above in gas separation.
[0025] According to the mixed matrix membrane of the present invention, the covalent organic skeleton is modified by using an ionic liquid with high solubility for carbon dioxide. The modified covalent organic skeleton not only has greatly improved permeability to carbon dioxide, but also has improved gas separation capability. It can still maintain good overall performance under different temperatures and pressures. During long-term operation, the separation performance of the mixed matrix membrane does not decay. It has excellent thermal stability and good long-term operation stability, and is particularly suitable for carbon dioxide gas separation, especially carbon dioxide and methane gas separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is the surface morphology of the mixed matrix membrane L1;
[0027] Figure 2 is the surface morphology of the mixed matrix membrane D1;
[0028] Figure 3 is the cross-sectional morphology of the mixed matrix membrane L1;
[0029] Figure 4 is the cross-sectional morphology of the mixed matrix membrane D1;
[0030] Figure 5 are the nitrogen adsorption-desorption curves of Dha Tab-COF framework and Dha Tab-COF framework modified with ionic liquid;
[0031] Figure 6 is the XRD pattern of Dha Tab-COF framework and Dha Tab-COF framework modified with ionic liquid;
[0032] Figure 7 is the pore size distribution diagram of Dha Tab-COF framework and Dha Tab-COF framework modified with ionic liquid;
[0033] Figure 8are the thermogravimetric images of mixed matrix membrane D1, mixed matrix membrane L1, and ionic liquid;
[0034] Fig. 9 It is the long-term operation stability image of mixed matrix membrane L1 and mixed matrix membrane D2. DETAILED DESCRIPTION
[0035] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0036] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0037] The mixed matrix membrane of the present invention contains a covalent organic framework modified by an ionic liquid and a block polyetheramide resin. The covalent organic framework modified by the ionic liquid not only reduces the pore size from 1.1-2.3 nanometers to 1.0-2.2 nanometers, which is beneficial to improving the gas screening ability, but also improves the solubility of carbon dioxide, thereby further improving the separation ability of the mixed matrix membrane for carbon dioxide.
[0038] In the mixed matrix membrane described in the present invention, the content of the ionic liquid modified covalent organic skeleton can be 0.1-20 weight parts, preferably 0.5-10 weight parts, more preferably 1-5 weight parts, and further preferably 1.5-2.5 weight parts relative to 100 weight parts of the block polyetheramide resin.
[0039] In the mixed matrix membrane of the present invention, in a preferred case, the ionic liquid modified covalent organic framework is a Dha Tab-COF framework modified by an ionic liquid. The modified Dha Tab-COF framework is loaded with an ionic liquid having a high solubility for carbon dioxide, which can simultaneously improve the permeability and selectivity of the membrane.
[0040] In the mixed matrix membrane of the present invention, during the modification process, the mass ratio of the Dha Tab-COF framework to the ionic liquid can be 1:(3-12), more preferably 1:(4-10), and even more preferably 1:(5-7).
[0041] In the mixed matrix membrane of the present invention, the ionic liquid can be an organic salt with high solubility in carbon dioxide commonly used in the art. In a preferred embodiment, the ionic liquid is at least one of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt and 1,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide salt.
[0042] In the mixed matrix membrane of the present invention, the thickness of the mixed matrix membrane may be 1.3-2.2 microns.
[0043] The method for preparing the mixed matrix membrane of the present invention comprises the following steps:
[0044] (1) modifying the covalent organic framework with an ionic liquid to obtain an ionic liquid-modified covalent organic framework;
[0045] (2) The ionic liquid-modified covalent organic framework is mixed with a block polyether amide resin solution, and the obtained mixture is coated on a porous base membrane, and then allowed to stand and dried.
[0046] In the method of the present invention, in step (1), the process of modifying the covalent organic framework with an ionic liquid comprises the following steps:
[0047] S1: vacuum treating the covalent organic framework;
[0048] S2: mixing the ionic liquid with the organic solvent, and mixing the obtained mixed liquid with the vacuum-treated covalent organic framework;
[0049] S3: The mixture obtained after the treatment in step S2 is centrifuged, and then the separated solid is washed and dried.
[0050] In the method of the present invention, in step S1, the covalent organic framework is preferably a Dha Tab-COF framework. The vacuum treatment conditions include: the temperature is preferably 90-120° C., and the time is preferably 20-28 hours. The covalent organic framework after vacuum treatment can empty the gas in the framework pores and better mix with the ionic liquid.
[0051] In the method of the present invention, in step S1, the Dha Tab-COF skeleton can be prepared by conventional technical means in the art. In some specific embodiments, the preparation method of the Dha Tab-COF skeleton includes: dissolving the reaction monomers 2,5-dihydroxyterephthalaldehyde and 1,3,5-tri(4-aminophenyl)benzene in a molar ratio of 3:(1.5-2.5) in a mixed solution of n-butanol and 1,2-dichlorobenzene, adding catalyst acetic acid, wherein the volume ratio of n-butanol, 1,2-dichlorobenzene and acetic acid is (4-6):(4-6):1; then sealing in an oxygen-free ampoule bottle and reacting at a temperature of 115-125°C for 50-100 hours; finally, the obtained reaction product is filtered and washed, extracted with tetrahydrofuran through a Soxhlet extractor, and dried to obtain the product Dha Tab-COF skeleton.
[0052] In the method of the present invention, in step S2, the mass ratio of the ionic liquid to the organic solvent can be 1: (20-30), preferably 1: (22-28). The mixing conditions of the ionic liquid and the organic solvent include: the temperature is preferably 25-35°C, and the time is preferably 20-40 minutes. In a preferred embodiment, the mixed liquid and the covalent organic framework are mixed by ultrasonic treatment, and the mixing conditions include: the temperature is preferably 25-35°C, and the time is preferably 0.5-1.5h.
[0053] In some specific embodiments, the centrifugal separation conditions in step S3 may include: centrifugal time 1-5 minutes, speed 6000-1600r / min. The solid washing conditions may include: detergent is methanol, washing times are 4-8 times. The solid drying conditions may include: temperature 70-100°C, time 10-14h.
[0054] The covalent organic framework modified with ionic liquid obtained according to the above process not only has its pore size reduced from 1.1-2.3 nanometers to 1.0-2.2 nanometers, which is beneficial to improving its gas screening ability, but also has improved solubility in carbon dioxide, thereby further improving the separation ability of the mixed matrix membrane for carbon dioxide.
[0055] In the method of the present invention, in step (1), the mass ratio of the covalent organic framework to the ionic liquid can be 1: (3-12), preferably 1: (4-10), and more preferably 1: (5-7). The covalent organic framework is preferably a Dha Tab-COF framework. The ionic liquid can be an organic salt with high solubility in carbon dioxide commonly used in the art, preferably at least one of 1-butyl-3-methylimidazolium bis (trifluoromethanesulfonyl) imide salt, 1-ethyl-3-methylimidazolium bis (trifluoromethanesulfonyl) imide salt and 1,3-dimethylimidazolium bis (trifluoromethanesulfonyl) imide salt.
[0056] In the method described in the present invention, in step (2), the mass ratio of the ionic liquid-modified covalent organic framework to the block polyetheramide resin is preferably (0.1-20):100, more preferably (0.5-10):100; further preferably (1-5):100, and most preferably (1.5-2.5):100.
[0057] In the method of the present invention, in step (2), the concentration of the block polyether amide resin solution may be 2-10 wt %, more preferably 4-6 wt %.
[0058] In the method of the present invention, in step (2), the block polyether amide resin solution can be prepared by conventional technical means in the art. In some specific embodiments, the method for preparing the block polyether amide resin solution comprises: adding block polyether amide resin particles to an organic solvent and heating and refluxing to dissolve the block polyether amide resin particles. Preferably, the block polyether amide resin particles are PEBAX-2533 particles.
[0059] In the method of the present invention, in step (2), the porous base membrane is preferably a polyvinylidene fluoride membrane supported by a polyester non-woven fabric. In some specific embodiments, the thickness of the polyester non-woven fabric is 90-110 microns, the thickness of the polyvinylidene fluoride layer is 30-40 microns, and the pore size range of the polyvinylidene fluoride layer is 0.08-0.1 microns.
[0060] The present invention also provides the use of the mixed matrix membrane described above in gas separation, and is particularly suitable for gas separation of carbon dioxide and methane.
[0061] The following examples further illustrate the mixed matrix membrane and its preparation method and application of the present invention. The examples are implemented based on the technical solution of the present invention, and provide detailed implementation methods and specific operation processes, but the protection scope of the present invention is not limited to the following examples.
[0062] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0063] Preparation Example 1
[0064] 24.9 mg of 2,5-dihydroxyterephthalaldehyde and 35.0 mg of 1,3,5-tri(4-aminophenyl)benzene were added to a heat-resistant glass tube, followed by 1 mL of 1,2-dichlorobenzene, 1 mL of n-butanol and 0.2 mL of acetic acid aqueous solution (6 mol / L) as a catalyst. After ultrasonication for 20 min, the heat-resistant glass tube was flame-sealed three times under 77k liquid nitrogen through freeze-vacuum cycles. The sealed glass tube was then reacted in an oven at 120°C for 72 hours. Finally, the generated product was collected by filtration, washed with acetone and tetrahydrofuran in turn, and then extracted with anhydrous tetrahydrofuran at 85°C for 48 hours. After the extract was vacuum dried at 100°C for 12 hours, the Dha Tab-COF skeleton was finally obtained.
[0065] Example 1
[0066] (1) 100 mg of the Dha Tab-COF skeleton in Preparation Example 1 was placed in a glass bottle and treated under vacuum conditions at 100° C. for 24 h to evacuate the gas in the pores. Subsequently, 0.6 g of 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt was added to 15 g of methanol solution, stirred at room temperature for 30 min, and then transferred to an ultrasonically treated glass bottle and ultrasonically treated at 30° C. for 1 h. The obtained mixture was centrifuged in a centrifuge at a speed of 8000 r / min for 2 minutes, and then the solid separated by centrifugation was washed 5 times with methanol to remove the ionic liquid on the outer surface of the Dha Tab-COF skeleton. Finally, the collected particles were dried at 80° C. for 12 h to obtain the Dha Tab-COF skeleton modified with ionic liquid.
[0067] (2) Dissolve 0.5 g of PEBAX-2533 (block polyetheramide resin particles, purchased from Collette Polymer (Shenzhen) Co., Ltd.) particles in 9.5 g of n-butanol and reflux at 80° C. for 2 h to obtain a 5 wt% block polyetheramide resin solution. Add 10 mg of the Dha Tab-COF skeleton prepared in step (1) to the block polyetheramide resin solution, ultrasonically treat at 30° C. for 30 minutes, and then stir at room temperature for 12 hours to mix. The obtained mixture is coated on a polyvinylidene fluoride membrane supported by a polyester non-woven fabric, left at room temperature for 48 hours, and then transferred to a vacuum drying oven at 60° C. and continued to dry for 24 hours to finally obtain a mixed matrix membrane L1. The polyvinylidene fluoride membrane supported by the polyester non-woven fabric has a polyester non-woven fabric as a support layer, the thickness of the polyester non-woven fabric is 100 microns, the thickness of the polyvinylidene fluoride layer is 35 microns, and the pore size range of the polyvinylidene fluoride is 0.08-0.1 microns.
[0068] Example 2
[0069] (1) 100 mg of the Dha Tab-COF skeleton in Preparation Example 1 was placed in a glass bottle and treated under vacuum conditions at 100° C. for 24 h to evacuate the gas in the pores. Subsequently, 0.6 g of 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt was added to 15 g of methanol solution, stirred at room temperature for 30 min, and then transferred to an ultrasonically treated glass bottle and ultrasonically treated at 30° C. for 1 h. The obtained mixture was centrifuged in a centrifuge at a speed of 8000 r / min for 2 minutes, and then the solid separated by centrifugation was washed 5 times with methanol to remove the ionic liquid on the outer surface of the Dha Tab-COF skeleton. Finally, the collected particles were dried at 80° C. for 12 h to obtain the Dha Tab-COF skeleton modified with ionic liquid.
[0070] (2) Dissolve 0.5 g of PEBAX-2533 (block polyetheramide resin particles, purchased from Colette Polymer (Shenzhen) Co., Ltd.) particles in 9.5 g of n-butanol and reflux at 80° C. for 2 h to obtain a 5 wt% block polyetheramide resin solution. Add 5 mg of the modified Dha Tab-COF skeleton prepared in step (1) to the block polyetheramide resin solution, ultrasonically treat at 30° C. for 30 minutes, and then stir at room temperature for 12 hours to mix. The obtained mixture is coated on a polyvinylidene fluoride membrane supported by a polyester non-woven fabric, left at room temperature for 48 h, and then transferred to a vacuum drying oven at 60° C. and continued to dry for 24 h to finally obtain a mixed matrix membrane L2. The polyvinylidene fluoride membrane supported by the polyester non-woven fabric has a polyester non-woven fabric as a support layer, the thickness of the polyester non-woven fabric is 100 microns, the thickness of the polyvinylidene fluoride layer is 35 microns, and the pore size range of the polyvinylidene fluoride is 0.08-0.1 microns.
[0071] Example 3
[0072] (1) 100 mg of the Dha Tab-COF skeleton in Preparation Example 1 was placed in a glass bottle and treated under vacuum conditions at 100° C. for 24 h to evacuate the gas in the pores. Subsequently, 0.6 g of 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt was added to 15 g of methanol solution, stirred at room temperature for 30 min, and then transferred to an ultrasonically treated glass bottle and ultrasonically treated at 30° C. for 1 h. The obtained mixture was centrifuged in a centrifuge at a speed of 8000 r / min for 2 minutes, and then the solid separated by centrifugation was washed 5 times with methanol to remove the ionic liquid on the outer surface of the Dha Tab-COF skeleton. Finally, the collected particles were dried at 80° C. for 12 h to obtain the Dha Tab-COF skeleton modified with ionic liquid.
[0073] (2) 0.5 g of PEBAX-2533 (block polyetheramide resin particles, purchased from Collette Polymer (Shenzhen) Co., Ltd.) particles were dissolved in 9.5 g of n-butanol and refluxed at 80° C. for 2 h to obtain a 5 wt% block polyetheramide resin solution. 15 mg of the modified Dha Tab-COF skeleton prepared in step (1) was added to the block polyetheramide resin solution, ultrasonically treated at 30° C. for 30 minutes, and then stirred at room temperature for 12 hours to mix. The obtained mixture was coated on a polyvinylidene fluoride membrane supported by a polyester non-woven fabric, left at room temperature for 48 h, and then transferred to a vacuum drying oven at 60° C. and continued to dry for 24 h to finally obtain a mixed matrix membrane L3. The polyvinylidene fluoride membrane supported by the polyester non-woven fabric has a polyester non-woven fabric as a support layer, the thickness of the polyester non-woven fabric is 100 microns, the thickness of the polyvinylidene fluoride layer is 35 microns, and the pore size range of the polyvinylidene fluoride is 0.08-0.1 microns.
[0074] Example 4
[0075] (1) 100 mg of the Dha Tab-COF skeleton in Preparation Example 1 was placed in a glass bottle and treated under vacuum conditions at 100° C. for 24 h to evacuate the gas in the pores. Subsequently, 0.6 g of 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt was added to 15 g of methanol solution, stirred at room temperature for 30 min, and then transferred to an ultrasonically treated glass bottle and ultrasonically treated at 30° C. for 1 h. The obtained mixture was centrifuged in a centrifuge at a speed of 8000 r / min for 2 minutes, and then the solid separated by centrifugation was washed 5 times with methanol to remove the ionic liquid on the outer surface of the Dha Tab-COF skeleton. Finally, the collected particles were dried at 80° C. for 12 h to obtain the Dha Tab-COF skeleton modified with ionic liquid.
[0076] (2) Dissolve 0.5 g of PEBAX-2533 (block polyetheramide resin particles, purchased from Colette Polymer (Shenzhen) Co., Ltd.) particles in 9.5 g of n-butanol and reflux at 80° C. for 2 h to obtain a 5 wt% block polyetheramide resin solution. Add 20 mg of the modified Dha Tab-COF skeleton prepared in step (1) to the block polyetheramide resin solution, ultrasonically treat at 30° C. for 30 minutes, and then stir at room temperature for 12 hours to mix. The obtained mixture is coated on a polyvinylidene fluoride membrane supported by a polyester non-woven fabric, left at room temperature for 48 h, and then transferred to a vacuum drying oven at 60° C. and continued to dry for 24 h to finally obtain a mixed matrix membrane L4. The polyvinylidene fluoride membrane supported by the polyester non-woven fabric has a polyester non-woven fabric as a support layer, the thickness of the polyester non-woven fabric is 100 microns, the thickness of the polyvinylidene fluoride layer is 35 microns, and the pore size range of the polyvinylidene fluoride is 0.08-0.1 microns.
[0077] Example 5
[0078] (1) 100 mg of the Dha Tab-COF skeleton in Preparation Example 1 was placed in a glass bottle and treated under vacuum conditions at 100° C. for 24 h to evacuate the gas in the pores. Subsequently, 0.6 g of 1-butyl-3-methylimidazole bistrifluoromethanesulfonyl imide salt was added to 15 g of methanol solution, stirred at room temperature for 30 min, and then transferred to an ultrasonically treated glass bottle and ultrasonically treated at 30° C. for 1 h. The obtained mixture was centrifuged in a centrifuge at a speed of 8000 r / min for 2 minutes, and then the solid separated by centrifugation was washed 5 times with methanol to remove the ionic liquid on the outer surface of the Dha Tab-COF skeleton. Finally, the collected particles were dried at 80° C. for 12 h to obtain the Dha Tab-COF skeleton modified with ionic liquid.
[0079] (2) 0.5 g of PEBAX-2533 (block polyetheramide resin particles, purchased from Colette Polymer (Shenzhen) Co., Ltd.) particles were dissolved in 9.5 g of n-butanol and refluxed at 80° C. for 2 h to obtain a 5 wt% block polyetheramide resin solution. 25 mg of the modified Dha Tab-COF skeleton prepared in step (1) was added to the block polyetheramide resin solution, ultrasonically treated at 30° C. for 30 minutes, and then stirred at room temperature for 12 hours to mix. The obtained mixture was coated on a polyvinylidene fluoride membrane supported by a polyester non-woven fabric, left at room temperature for 48 h, and then transferred to a vacuum drying oven at 60° C. and continued to dry for 24 h to finally obtain a mixed matrix membrane L5. The polyvinylidene fluoride membrane supported by the polyester non-woven fabric has a polyester non-woven fabric as a support layer, the thickness of the polyester non-woven fabric is 100 microns, the thickness of the polyvinylidene fluoride layer is 35 microns, and the pore size range of the polyvinylidene fluoride is 0.08-0.1 microns.
[0080] Comparative Example 1
[0081] 0.5g of PEBAX-2533 (block polyetheramide resin particles, purchased from Colette Polymer (Shenzhen) Co., Ltd.) particles were dissolved in 9.5g of n-butanol and refluxed at 80°C for 2h to obtain a 5wt% block polyetheramide resin solution. The block polyetheramide resin solution was coated on a polyvinylidene fluoride based membrane, left at room temperature for 48h, and then transferred to a vacuum drying oven at 60°C for further drying for 24h to finally obtain a mixed matrix membrane D1. The polyvinylidene fluoride based membrane has a polyester non-woven fabric as a support layer, the thickness of the polyester non-woven fabric is 100 microns, the thickness of the polyvinylidene fluoride layer is 35 microns, and the pore size range of the polyvinylidene fluoride is 0.08-0.1 microns.
[0082] Comparative Example 2
[0083] (1) 100 mg of the DhaTab-COF skeleton prepared in Preparation Example 1 was placed in a glass bottle and treated under vacuum conditions at 100°C for 24 h to exhaust the gas in the pores.
[0084] (2) 0.5 g of PEBAX-2533 (block polyetheramide resin particles, purchased from Colette Polymer (Shenzhen) Co., Ltd.) particles were dissolved in 9.5 g of n-butanol and refluxed at 80° C. for 2 h to obtain a 5 wt% block polyetheramide resin solution. 10 mg of the modified Dha Tab-COF skeleton prepared in step (1) was added to the block polyetheramide resin solution, ultrasonically treated at 30° C. for 30 minutes, and then stirred at room temperature for 12 hours to mix. The obtained mixture was coated on a polyvinylidene fluoride membrane supported by a polyester non-woven fabric, left at room temperature for 48 h, and then transferred to a vacuum drying oven at 60° C. and continued to dry for 24 h to finally obtain a mixed matrix membrane D2. The polyvinylidene fluoride membrane supported by the polyester non-woven fabric has a polyester non-woven fabric as a support layer, the thickness of the polyester non-woven fabric is 100 microns, the thickness of the polyvinylidene fluoride layer is 35 microns, and the pore size range of the polyvinylidene fluoride is 0.08-0.1 microns.
[0085] Test Example 1
[0086] The mixed matrix membrane was first frozen in liquid nitrogen for one hour, then quenched and gold-sprayed using tweezers, and finally the surface morphology and cross-sectional morphology of the mixed matrix membrane were observed under a scanning electron microscope (Carl Zeiss, Germany, ZEISS model).
[0087] Figure 1 The figure shows the surface morphology of the mixed matrix membrane L1 of Example 1. It can be seen from the image that the membrane is dense and has no defects. Figure 2 This is a surface morphology image of the mixed matrix membrane D1 prepared in Comparative Example 1. From the image, it can be seen that the membrane exhibits a typical polymer membrane morphology, which is dense and defect-free. Figure 3The figure shows the cross-sectional morphology of the mixed matrix membrane L1 of Example 1, in which the thickness of the separation layer is 2.2 μm. Figure 4 This is a cross-sectional morphology diagram of the mixed matrix membrane D1 prepared in Comparative Example 1. From the cross-sectional image, it can be seen that the segmented polyetheramide resin separation layer is tightly bonded to the polyvinylidene fluoride support layer, the interface is clear, and the thickness of the segmented polyetheramide resin separation layer is 0.8 microns.
[0088] Test Example 2
[0089] (1) Weigh 0.1 g of the Dha Tab-COF framework prepared in Preparation Example 1 and 0.1 g of the Dha Tab-COF framework modified with ionic liquid prepared in Example 1, and dry them under vacuum at 100° C. for 12 hours.
[0090] (2) The two samples were then subjected to BET nitrogen adsorption and desorption tests at 77K liquid nitrogen, respectively, and the test method was as follows: The specific surface area of the Dha Tab-COF framework was measured using a N2 physical adsorption / desorption instrument (Micromeritics, ASAP 2460, USA). Before the test, the Dha Tab-COF framework was degassed in a vacuum at 100°C for 12 hours to remove the residual moisture and organic solvent in the pores of the Dha Tab-COF framework.
[0091] Figure 5 The nitrogen adsorption-desorption curves of the Dha Tab-COF framework prepared in Preparation Example 1 and the Dha Tab-COF framework modified with ionic liquid prepared in Example 1. According to the images, both are typical type IV isotherms, indicating that the Dha Tab-COF framework and the modified Dha Tab-COF framework are both mesoporous materials.
[0092] Test Example 3
[0093] The Dha Tab-COF skeleton was ground into fine powder using a mortar. An X-ray diffractometer (Rigaku Corporation, D / max-2550X) was used, with a scanning range of 2° to 40° at a test wavelength of λ=0.154059nm, and a scanning speed of 5° / min. The interlayer spacing of the Dha Tab-COF skeleton and the specific values of the chain spacing of the membrane were then calculated using the Bragg equation (λ=2d sinθ).
[0094] Figure 6The XRD patterns of the Dha Tab-COF framework prepared in Preparation Example 1 and the Dha Tab-COF framework modified with ionic liquid prepared in Example 1. According to the spectrum, it can be seen that the Dha Tab-COF framework has high crystallinity, and the position of the diffraction peak does not change after loading the ionic liquid, which indicates that the Dha Tab-COF framework still maintains a complete crystal structure, but the intensity of the diffraction peak decreases, which is because the disordered distribution of the ionic liquid in the Dha Tab-COF framework causes its internal electron density to change.
[0095] Test Example 4
[0096] The test method for pore size distribution is the same as the test method for specific surface area in Test Example 2.
[0097] Figure 7 The pore size distribution diagram of the Dha Tab-COF framework prepared in Preparation Example 1 and the Dha Tab-COF framework modified with ionic liquid prepared in Example 1. The BET surface area of the modified Dha Tab-COF framework is calculated to be 150.9 m 2 / g, 601m of the original Dha Tab-COF skeleton 2 / g has decreased. Through density functional theory calculations, the pore size of the modified Dha Tab-COF skeleton is mainly distributed in the range of 1.0-2.2 nanometers, which is smaller than the 1.1-2.3 nanometers of the original Dha Tab-COF skeleton. The reduction in pore size will help improve the gas screening ability.
[0098] Test Example 5
[0099] The thermal stability of the mixed matrix membrane was measured using a thermal analyzer (TA Instruments, USA, TGA-2050), with the temperature test range from room temperature to 800°C and a heating rate of 10°C / min. In the thermal stability test of the mixed matrix membrane, homogeneous membranes were used for testing, excluding PVDF-based membranes.
[0100] Figure 8 The thermogravimetric images of the mixed matrix membrane D1 prepared in Comparative Example 1, the mixed matrix membrane L1 prepared in Example 1, and the ionic liquid are shown. As can be seen from the figure, the mixed matrix membrane L1 can remain stable at up to 250° C. and has excellent thermal stability.
[0101] Test Example 6
[0102] Fig. 9The long-term operation stability images of the mixed matrix membrane L1 prepared in Example 1 and the mixed matrix membrane D2 prepared in Comparative Example 2 are shown. The mixed matrix membrane L1 and the mixed matrix membrane D2 were tested for stability for up to 20 days at an operating pressure of 2 bar and an operating temperature of 15°C. From the figure, it can be seen that the CO2 / CH4 separation performance of the membrane is relatively stable without attenuation. Although the carbon dioxide permeability coefficient fluctuates slightly, it is still above 260 Barre, indicating that the Dha Tab-COF skeleton and the ionic liquid do not damage the polymer matrix, which confirms that the mixed matrix membrane in the present invention has good long-term operation stability.
[0103] Test Example 7
[0104] The test was conducted at 15°C using 50% / 50% (vol / vol) CO2 / CH4 feed gas, H2 as carrier gas, a carrier gas flow rate of 40 mL / min, a test gas flow rate of 20 mL / min, and a back pressure valve to control the pressure difference before and after the membrane to 2 bar. The gas separation performance of the mixed matrix membranes of Examples 1-15 and Comparative Examples 1-2 was measured, and the results are shown in Table 1:
[0105] Table 1
[0106]
[0107] As can be seen from Table 1, within the preferred range, the permeability coefficient of the mixed matrix membrane of the present invention to carbon dioxide is as high as 230 or more, and the selectivity to carbon dioxide and methane is also above 23, indicating that the mixed matrix membrane has excellent permeability while also taking into account high selectivity. Specifically, this is because the pores of the Dha Tab-COF skeleton modified with ionic liquid are reduced, and these pores can provide additional channels for the transmission of carbon dioxide, and the Dha Tab-COF skeleton and the ionic liquid in the skeleton have a higher affinity for carbon dioxide gas molecules and can preferentially bind to carbon dioxide, which to a certain extent enhances the permeability and selectivity of the Dha Tab-COF skeleton to carbon dioxide, and is particularly suitable for gas separation of carbon dioxide and methane.
[0108] Test Case 8
[0109] Under the conditions of an experimental temperature of 15-35°C, a constant feed pressure of 2 bar, H2 as a carrier gas, a carrier gas flow rate of 40 mL / min, and an experimental gas CO2 and CH4 flow rate of 20 mL / min, the permeation performance and separation performance of the mixed matrix membrane L1 prepared in Example 1 were tested. The results are shown in Table 2:
[0110] Table 2
[0111] serial number Temperature(℃) <![CDATA[CO2 Permeability Coefficient (Barrer)]]> <![CDATA[CH4 Permeability Coefficient (Barrer)]]> <![CDATA[CO2 / CH4 selectivity]]> L1 15 281 6.0 46.8 L1 20 288 6.5 43.9 L1 25 294 7.1 41.2 L1 30 296 7.4 39.8 L1 35 305 7.9 38.6 D1 15 203 19.7 10.3
[0112] It can be seen from Table 2 that even if the temperature rises, the carbon dioxide coefficient of the mixed matrix membrane in the present invention remains above 280, and the CO2 / CH4 selectivity is also above 35, which is far better than the performance of the mixed matrix membrane in the comparative example, demonstrating the excellent thermal stability of the mixed matrix membrane in the present invention.
[0113] Test Example 9
[0114] The experimental temperature was fixed at 15°C, H2 was used as the carrier gas, the carrier gas flow rate was 40 mL / min, CO2 and CH4 were used as the experimental gases, the experimental gas flow rates were both 20 mL / min, and the pressure difference before and after the membrane was adjusted in the range of 2-6 bar by the back pressure valve, and the gas separation performance of the mixed matrix membrane L1 prepared in Example 1 was tested. The results are shown in Table 3:
[0115] Table 3
[0116] serial number Pressure(bar) <![CDATA[CO2 Permeability Coefficient (Barrer)]]> <![CDATA[CH4 Permeability Coefficient (Barrer)]]> <![CDATA[CO2 / CH4 selectivity]]> L1 2 281 6.0 46.8 L1 3 188 8.5 22.1 L1 4 169 9.7 17.4 L1 5 165 10.1 16.3 L1 6 161 10.5 15.3 D1 2 203 19.7 10.3
[0117] It can be seen from Table 3 that with the increase of pressure, the CO2 / CH4 selectivity of the mixed matrix membrane decreases, but even under a high pressure of 6 bar, the CO2 / CH4 selectivity of the mixed matrix membrane in the present invention is above 15, which is better than the overall performance of the mixed matrix membrane in the comparative example.
[0118] pass Figure 1-9 It can be seen from the results in Tables 1-3 that the mixed matrix membrane of the present invention uses ionic liquid to modify the covalent organic framework, has high permeability and excellent selectivity, and is particularly suitable for gas separation of carbon dioxide and methane. Moreover, under different temperatures and pressures, the mixed matrix membrane can still maintain good overall performance, and the separation performance of the mixed matrix membrane does not decay under long-term operation, and has excellent thermal stability and good long-term operation stability.
[0119] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A mixed matrix membrane, characterized in that The mixed matrix membrane contains an ionic liquid modified covalent organic backbone and a segmented polyetheramide resin.
2. The mixed matrix membrane according to claim 1, characterized in that Relative to 100 parts by weight of the block polyetheramide resin, the content of the ionic liquid-modified covalent organic framework is 0.1-20 parts by weight, preferably 1-5 parts by weight.
3. The mixed matrix membrane according to claim 1 or 2, characterized in that The ionic liquid modified covalent organic framework is a Dha Tab-COF framework modified by ionic liquid; Preferably, during the modification process, the mass ratio of the Dha Tab-COF framework to the ionic liquid is 1:(3-12), preferably 1:(5-7).
4. The mixed matrix membrane according to claim 3, characterized in that The ionic liquid is at least one of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and 1,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide.
5. The mixed matrix membrane according to any one of claims 1 to 4, characterized in that The thickness of the mixed matrix membrane is 1.3-2.2 microns.
6. A method for preparing a mixed matrix membrane, characterized in that: The method comprises the following steps: (1) modifying the covalent organic framework with an ionic liquid to obtain an ionic liquid-modified covalent organic framework; (2) The ionic liquid-modified covalent organic framework is mixed with a block polyether amide resin solution, and the obtained mixture is coated on a porous base membrane, and then allowed to stand and dried.
7. The method according to claim 6, characterized in that In step (1), the process of modifying the covalent organic framework with an ionic liquid comprises the following steps: S1: vacuum treating the covalent organic framework; S2: mixing the ionic liquid with the organic solvent, and mixing the obtained mixed liquid with the vacuum-treated covalent organic framework; S3: The mixture obtained after the treatment in step S2 is centrifuged, and then the separated solid is washed and dried.
8. The method according to claim 7, characterized in that The mass ratio of the covalent organic framework to the ionic liquid is 1:(3-12), preferably 1:(5-7); Preferably, the covalent organic framework is a Dha Tab-COF framework; Preferably, the ionic liquid is at least one of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide and 1,3-dimethylimidazolium bis(trifluoromethanesulfonyl)imide.
9. The preparation method according to any one of claims 6 to 8, characterized in that: In step (2), the mass ratio of the ionic liquid modified covalent organic framework to the block polyetheramide resin is (0.1-20):100, preferably (1-5):100; Preferably, the concentration of the block polyetheramide resin solution is 2-10 wt %, more preferably 4-6 wt %.
10. The preparation method according to claim 6 or 9, characterized in that: In step (2), the porous base membrane is a polyvinylidene fluoride membrane supported by a polyester non-woven fabric.
11. Use of the mixed matrix membrane according to any one of claims 1 to 10 in gas separation.
Citation Information
Patent Citations
Porous solid supported ionic liquid for adsorption of HCl gas
CN107651651A
Mixed matrix membrane for gas separation and preparation method and application thereof
CN115970524A
Mixed matrix membrane containing soluble porous organic cage IL (at) CC3 for gas separation as well as preparation method and application of mixed matrix membrane
CN116036897A
Preparation and application of high-performance mixed matrix gas separation membrane based on ionic liquid coordination
CN116351265A
Dha Ta-COF-coated PEBAX mixed matrix membrane as well as preparation method and application of Dha Ta-COF-coated PEBAX mixed matrix membrane
CN117959944A
Cited By
Imidazolyl covalent organic framework hybrid membrane as well as preparation method and application thereof
CN120502246A